Genetic susceptibility of bladder cancer in the Lebanese population - Hampig Raphael Kourie; Bahaa Succar; Eliane Chouery; Cybel Mehawej; Nizar Ahmadieh; Joseph Zouein; Avedis Mardirossian; Nadine Jalkh; Ghassan Sleilaty; Joseph Kattan; Elie Nemr (BMC Medical Genomics, 2022)
Abstract Background Bladder cancer (BC) is the 10th most frequent tumor worldwide. Evidence shows an association between elevated risk of BC and various single nucleotide polymorphisms (SNP). BC incidence was the highest in Lebanon according to Globocan 2018 report, but little is known about the genetic susceptibility of Lebanese people to this disease. We aim to evaluate whether this prominent incidence of BC in Lebanon is attributable to known coding genetic variants. Methods A case-control study was conducted at Hotel-Dieu de France Hospital, Beirut. A cohort of 51 Lebanese patients with BC were recruited between 2017 and 2020. Whole Exome Sequencing (WES) was performed on peripheral blood samples to detect coding genetic variants in the patients. An in-house database including WES data from 472 Lebanese individuals served as control. Literature review of the genetic predisposition to BC was conducted to establish a database of variants known to influence the risk of BC. In-common SNPs were identified between cases and the aforecited database, and their allelic frequencies was quantified in the former and in controls. Comparative analysis of the allelic frequencies of each in-common SNP was carried out between cases, controls, and the genome aggregation database (gnomAD). Analysis was performed by applying the binomial law and setting the p-value to 10− 10. Results 484 polymorphisms associated with BC were extracted from the literature review ;151 of which were in-common with the 206 939 variations detected by WES in our cases. Statistically significant differences (p-value < 10− 10) in allelic frequencies was seen in 11 of the 151 in-common SNPs, but none of which corresponds with a higher BC risk. Moreover, rs4986782 variant in the NAT1 gene is not associated with BC in the Lebanese population. `. Conclusion This is the first next-generation sequencing (NGS)- based study investigating BC risk in a Lebanese cohort of 51 patients. The majority of known exonic variants in the literature were not associated with BC in our patients. Further studies with larger sample sizes are warranted to explore the association of BC in our population with known non-coding genetic variants, and the remainder of WES-generated private Lebanese variants.